HUBUNGAN UMUR DAN PENGETAHUAN REMAJA PUTRI TERHADAP DETEKSI DINI CARCINOMA MAMMAE PADA SISWI KELAS X DI SMA BAKTI KELUARGA KOTA LUBUK LINGGAU - Meriaya Sari, Lely; Turiyani; Veradilla (LPPM STIKes Mitra Adiguna, 2025)
Carcinoma Mammae is the main factor of death from all cancers that occur in Indonesian women. This study aims to determine the relationship between age and knowledge of female students towards early detection of Carcinoma Mammae at SMA Bakti Keluarga, Lubuk Linggau City in 2025. This study utilized an Analytical Survey with a Cross Sectional approach. The population was female students of class X of SMA Bakti Keluarga, Lubuk Linggau City in 2025 and the sample was taken using the Total sampling technique, totaling 40 people. The measuring instrument was a questionnaire. The results of the univariate analysis found that from 40 female adolescents, it was found that there were 31 early female adolescents (77.5%) and 9 late female adolescents (22.5%) and it was found that female adolescents with good knowledge were 25 respondents (62.5%) and female students with poor knowledge were 15 respondents (37.5%). Bivariate analysis shows that the age of adolescent girls has a significant relationship with early detection of Breast Carcinoma (p value 0.002) and the knowledge of adolescent girls has a significant relationship with early detection of Breast Carcinoma (p value 0.001). The conclusion is that there is a relationship between the age and knowledge of adolescent girls with early detection of Breast Carcinoma.